Variation in Reproductive Investment among Ohio Reservoir Largemouth Bass Populations. Issue 5 (30th July 2020) - Pritt, Jeremy J.; Zweifel, Richard D.; Tyszko, Stephen M.; Conroy, Joseph D.
Abstract: Reproductive investment, expressed in terms of fecundity and egg quality produced by individual female fish, varies among populations for many species, reflecting plasticity in life history strategies related to intraspecific density dependence or environmental variability. Fisheries scientists and managers have long sought to understand differences in Largemouth Bass Micropterus salmoides population dynamics, yet basic life history traits, such as variation in reproductive investment, remain largely unknown. We determined the fecundity–weight and ovary energy density–weight relationships (where fecundity indexes egg quantity and ovary energy density indexes egg quality) for Largemouth Bass populations from 19 Ohio reservoirs and examined factors that were correlated with population‐specific differences. We found that both relationships varied among reservoir populations, with some interannual variation in reservoirs sampled in multiple years. We then related fecundity and ovary energy density to (1) population characteristics, including population density (as indexed by standard shoreline boat electrofishing CPUE, fish/h) and growth (as indexed by the growth coefficient k from the von Bertalanffy growth function); and (2) reservoir characteristics, including reservoir size (as surface area) and productivity (as Secchi transparency depth). We found that populations with greater fecundity also exhibited greater ovary energy density, indicating that the quantity and quality of reproductive output were greater in some populations than in others. Populations with high reproductive investment were associated with low Largemouth Bass density, fast growth, large reservoir size, and high productivity (i.e., low Secchi transparency). The among‐population variation in reproductive investment provides evidence of density‐dependent control of fecundity and egg quality.